Temperature-dependent conformational changes in Arabidopsis DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN 2A - Tähtinen, Petri; Fujii, Hiroaki (Springer Science and Business Media LLC, 2025)
With the recent rise in global temperatures, understanding plant heat stress responses has become an urgent challenge. The DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN 2A (DREB2A) is one of the key transcription factors involved in plant responses to heat stress. Previous studies show that DREB2A degrades at 23 degrees C, while it accumulates at 37 degrees C in Arabidopsis, leading to heat-induced gene expression. However, the direct impact of temperature on DREB2A protein itself remains insufficiently understood. This study investigates the effect of temperature on the DREB2A protein by expressing recombinant DREB2A in Escherichia coli. Results demonstrate that DREB2A accumulates in E. coli at 37 degrees C but not at 23 degrees C, a pattern also observed in Arabidopsis, despite the differences between these organisms. Circular dichroism (CD) spectroscopy further revealed structural alterations in DREB2A between 23 degrees C and 37 degrees C, though specific details remain unclear. Taken together, these findings suggest that temperature-induced conformational changes occur in DREB2A between 23 degrees C and 37 degrees C, which may play a role in regulating its stability. This knowledge also indicates that 37 degrees C-induced stability is a contributing factor to successful purification of full-length recombinant DREB2A protein.